Estimating the Burden of Cancer and Treatment Cost Related to Alcohol Consumption in Indonesia: a Descriptive Study - Kristina, Susi Ari (Asian Pac J Cancer Prev, 2018)
BACKGROUND: Alcohol consumption has become one of the most common cancer risk factors after smoking. Nowadays, estimation of the burden of disease attributable to alcohol has become standard in documenting the impact of health problems, but it has been rarely performed in Indonesia. The aim of this study was to estimate treatment cost of cancer related to alcohol consumption among the Indonesian population. METHODS: This research design was descriptive with a prevalence-based approach using secondary data. Proportions of cancers were calculated using an alcohol-attributable fractions (AAF) formula. Treatment costs for eight types of cancer were assessed according to average treatment cost per patient from the national universal health coverage database for 2016. RESULT: The top three AAFs for males were cancers of the pharynx, esophagus and larynx (17.5%, 15.3% and 7.98%, respectively), while in females they were cancers of the esophagus, pharynx and stomach (2.15%; 1.39%; 0.83%). Among the eight types of cancer studied, the highest incidence in males was noted for liver cancer (132 cases) while colorectal cancer was the most common among females (31 cases). Treatment cost for cancers related to alcohol consumption were highest for colorectak cancer followed by laryngeal and liver cancer (116,083, 98,325 and 93,253 USD, respectively. CONCLUSION: The expenditure for treatment of cancers related to alcohol consumption accounts for about 1.71% of total cancer treatment cost. Since cancers related to alcohol consumption can be considered having an economic impact in Indonesia, it becomes important for the government to control alcohol consumption so that related healthcare expenditure can be minimized.